Book Review:Leonora NEVILLE, Anna Komnene: The Life and Work of a Medieval Historian, Oxford: Oxford University Press, 2016 - SiMPSON, Alicia Josephine (Byzantina Symmeikta, 2018)
Book Review:Leonora Neville, Anna Komnene: The Life and Work of a Medieval Historian, Oxford: Oxford University Press, 2016